Cytosine Base Editor (hA3A-BE3-NG)-Mediated Multiple Gene Editing for Pyramid Breeding in Pigs - Wang, Yu; Bi, Dengfeng; Qin, Guosong; Song, Ruigao; Yao, Jing; Cao, Chunwei; Zheng, Qiantao; Hou, Naipeng; Wang, Yanfang; Zhao, Jianguo (Frontiers in Genetics, 2020)
Pig is an important agricultural economic animal, providing large amount of meat products. With the development of functional genomics and bioinformatics, lots of genes and functional single nucleotide polymorphism (SNPs) related to disease resistance and (or) economic traits in pigs have been identified which provides the targets for genetic improvement by genome editing. Base editors (BEs), combining Cas9 nickase and cytidine or adenine deaminase, achieve all four possible transition mutations (C to T, A to G, T to C and G to A) efficiently and accurately without double strand breaks (DSBs) under the protospacer adjacent motif (PAM) sequence of NGG. However, the NGG PAM in canonical CRISPR-Cas9 can only cover approximately 33% in the whole genome which limits its broad application. In the current study, hA3A-BE3-NG system was constructed with the fusion of SpCas9-NG variant and hA3A-BE3 to create C-to-T conversion at NGN PAM sites efficiently. The editing efficiency and scope of hA3A-BE3-NG was confirmed in HEK293T cells and porcine fetal fibroblast (PFF) cells. Results showed that the efficiency of hA3A-BE3-NG was much higher than that of hA3A-BE3 on NGH (H = A, C or T) PAM sites (21.27% vs. 2.81% at average). Further, nonsense and missense mutations were introduced efficiently and precisely via hA3A-BE3-NG in multiple pig economic trait related genes (CD163, APN, MSTN and MC4R) in PFF cells by one transfection. The current work indicates the potential applications of hA3A-BE3-NG for pyramiding breeding studies in livestock.